Sex-specific patterns in body mass and mating system in the Siberian flying squirrel. Issue 1 (December 2016) - Selonen, Vesa; Wistbacka, Ralf; Santangeli, Andrea
Abstract Background Reproductive strategies and evolutionary pressures differ between males and females. This often results in size differences between the sexes, and also in sex-specific seasonal variation in body mass. Seasonal variation in body mass is also affected by other factors, such as weather. Studies on sex-specific body mass patterns may contribute to better understand the mating system of a species. Here we quantify patterns underlying sex-specific body mass variation using a long-term dataset on body mass in the Siberian flying squirrel, Pteromys volans . Results We show that female flying squirrels were larger than males based on body mass and other body measures. Males had lowest body mass after the breeding season, whereas female body mass was more constant between seasons, when the pregnancy period was excluded. Male body mass did not increase before the mating season, despite the general pattern that males with higher body mass are usually dominant in squirrel species. Seasonal body mass variation was linked to weather factors, but this relationship was not straightforward to interpret, and did not clearly affect the trend in body mass observed over the 22 years of study. Conclusions Our study supports the view that arboreal squirrels often deviate from the general pattern found in mammals for larger males than females. The mating system seems to be the main driver of sex-specific seasonal body mass variation in flying squirrels, and conflicting selective pressure may occur for males to have low body mass to facilitate gliding versus high body mass to facilitate dominance.